2010
DOI: 10.1136/gut.2010.208348
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-binding lectin deficiency results in unusual antibody production and excessive experimental colitis in response to mannose-expressing mild gut pathogens

Abstract: These results suggest that systemic MBL helps to prevent excessive inflammation upon access of normally mild pathogens across the damaged intestinal epithelium. Lack of this innate defence promotes antibody responses with cross-reactive potential against common mannan epitopes. These interpretations are compatible with the increased prevalence of ASCA and complicated disease phenotypes in MBL-deficient patients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 50 publications
0
32
1
Order By: Relevance
“…This lectin is pivotal in intestinal inflammation and host defense by modulating the inflammatory mediator responses (Th1/Th17) and amplifying the expression of certain receptors (dectin-1 and TLR-4). Although Muller et al 16 showed that MBL expression was virtually undetectable in the intestinal mucosa from healthy subjects or patients with CD, our study using Caco-2 human colorectal cells stimulated with different PPARg agonists (amino-phenyl-methoxy-propionic acid, 5-aminosalycilate, or pioglitazone) showed a high expression of MBL-2 mRNA by microarray and quantitative reverse transcriptase-PCR analyses (see Supplementary Data online). Of note, PPARg contributes to increased recognition and phagocytosis of unopsonized C. albicans and PPARg activation reduces C. albicans colonization in the murine digestive tract.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This lectin is pivotal in intestinal inflammation and host defense by modulating the inflammatory mediator responses (Th1/Th17) and amplifying the expression of certain receptors (dectin-1 and TLR-4). Although Muller et al 16 showed that MBL expression was virtually undetectable in the intestinal mucosa from healthy subjects or patients with CD, our study using Caco-2 human colorectal cells stimulated with different PPARg agonists (amino-phenyl-methoxy-propionic acid, 5-aminosalycilate, or pioglitazone) showed a high expression of MBL-2 mRNA by microarray and quantitative reverse transcriptase-PCR analyses (see Supplementary Data online). Of note, PPARg contributes to increased recognition and phagocytosis of unopsonized C. albicans and PPARg activation reduces C. albicans colonization in the murine digestive tract.…”
Section: Discussionmentioning
confidence: 51%
“…These observations provide in vivo evidence that MBL contributes to innate immune protection in the stomach, lungs, and kidneys and are similar to those of another study that showed an increase in fungal burden in the kidney and lungs of MBL-KO mice. 16 In the mouse model of IC, MBL deficiency was strongly associated with increased C. albicans infections. 20 MBL can also modulate inflammatory mediators, in particular IL-1b and IL-6, which have an important role in the development of intestinal inflammation and show a dramatic increase in the colonic mucosa during disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBL plays an important role in human innate immunity by binding to mannan epitopes on the surfaces of microorganisms 28. Lack of MBL was found to promote a systemic adaptive immune response in mice treated with Candida albicans and was associated with higher ASCA levels in both mice and patients with CD 29 30 . Candida albicans has been shown to generate ASCAs due to the expression of similar cell wall mannan epitopes as the yeast Saccharomyces cerevisiae 31 32.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent study showed antibody against outer membrane inhibits the motility of Leptospira (Guo et al 2012), which provides a novel view and understanding of immune response to leptospiral infection. It is well known that Leptospira are readily opsonized and phagocytized by macrophages and neutrophils, while undergoing lysis once the complements are present (Adler and Faine 1978;Kuhlman et al 1989;Masuzawa et al 1996;Müller et al 2010). However, there is no study on the inhibitory effect of MBL on the motility of Leptospira.…”
Section: Introductionmentioning
confidence: 94%